Determinants of Electronic Medical Record Closing Delays: A HOT-Fit Approach - Marian Tonis Rian; Marido Bisra; Wiwik Suryandartiwi (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: Timely completion of Electronic Medical Records (EMR) is essential for ensuring continuity of care, administrative efficiency, and hospital accreditation compliance. However, delays in EMR closing remain a common problem in hospital services.. Methods: A quantitative cross-sectional study was conducted among 150 healthcare professionals involved in EMR documentation processes. Data were collected using structured questionnaires based on HOT-Fit dimensions, including human, organizational, and technological factors. Data were analyzed using descriptive statistics, correlation tests, and multiple linear regression analysis. Results: Human factors (β = -0.241; p = 0.002), organizational factors (β = -0.398; p < 0.001), and technological factors (β = -0.219; p = 0.004) significantly influenced EMR closing delays. Organizational factors were identified as the strongest predictor. The regression model explained 56.4% of the variance in EMR closing delays (Adjusted R² = 0.564). Better alignment between human, organizational, and technological components was associated with improved EMR closing timeliness. Conclusion: EMR closing delays are influenced by multidimensional factors involving human, organizational, and technological components. Strengthening organizational support, improving user competency, and optimizing EMR system performance are important strategies to reduce delays and improve hospital service quality.